The relationship of the ratio of platelet distribution width to serum albumin with kidney disease progression in patients with hypertension - Kenichi Tanaka; Hiroshi Kimura; Hirotaka Saito; Michio Shimabukuro; Koichi Asahi; Tsuyoshi Watanabe; Junichiro James Kazama (Scientific Reports)
Abstract Platelet distribution width (PDW), which represents the heterogeneity of platelet size, can predict a poor prognosis in various populations. However, the PDW-to-serum albumin ratio (PAR) has not been evaluated in any disease population, and whether the PAR could be a prognostic marker in hypertension remains unknown. The relationship between the PAR and adverse outcomes was examined retrospectively using longitudinal data of 1,578 patients with hypertension from the Fukushima Cohort Study. Participants were categorized into tertiles by baseline PAR. The primary endpoint of the present study was a kidney event, defined as a combination of a 50% decline in eGFR from baseline and end-stage kidney disease requiring kidney replacement therapy. During the median follow-up period of 5.4 years, 146 patients had kidney events. The higher PAR group (tertile 3) showed an increased incidence of kidney events on Kaplan–Meier curve analysis. Compared with the lowest PAR tertile, the highest PAR tertile (tertile 3) showed a significantly higher risk of kidney events (adjusted hazard ratio 3.74, 95% confidence interval (CI) 1.65–8.48). Similar relationships were observed for risks of all-cause death and cardiovascular events. The predictive value of the PAR for kidney events was superior to that of PDW alone. The areas under the curves for PDW and the PAR were 0.61 (95% CI 0.56–0.66) and 0.77 (95% CI 0.74–0.81), respectively (P < 0.001). The PAR could be a useful predictive marker of adverse outcomes in this population.